Studi Kasus Penutupan GKI Yasmin diKelurahan Curug, Kecamatan Bogor Barat Kota Bogor - Anis, Sevtian Inayah (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2025)
This journal discusses conflict resolution and analyzes the dynamics of discrimination in the context of the closure of GKI Yasmin in Curug Village, West Bogor District, Bogor City. The dynamics of discrimination that occurred in the GKI Yasmin case show tension between the constitutional rights of minority groups and pressure from the majority group. The closure of this church not only affected the GKI Yasmin congregation, but also created social tension in the surrounding community. This highlights the need for more inclusive and fair public policies to guarantee equal rights for all groups, regardless of religious background. The case that became a national spotlight because it involved the issue of the right to worship, conflict between residents, and attracted the interests of the local government and community groups. The research method used was interviews with local residents, the results of the study showed that the closure of GKI Yasmin was triggered by a dispute over church building permits, pressure from certain groups, and the uncertainty of the local government in guaranteeing religious freedom according to the constitution. This study emphasizes the importance of the government in upholding human rights and the need for a conflict resolution mechanism based on dialogue between residents to prevent religious discrimination in the future.